Perancangan Sistem Informasi Point Of Sales Berbasis Web Pada Perusahaan Sablon - Fitra Adhitya Sandi; Laila Septiana (LPPM Universitas Bina Sarana Informatika, 2021)
The sales system that runs on CV. Wadas Warna Warni (Dyotees) is currently still done conventionally, according to the author's observation, it is very ineffective, where Customer Service has to make a conventional order form using Microsoft Excel which contains details of sales and sales calculations, then prints the order form and also disposes the order form. to the production, invoice creation and calculation which is still done conventionally using Microsoft Excel. This causes frequent input errors, data redundancies and also takes a long time to position orders to the production department, it is difficult to monitor sales that are being processed or have finished processing production and requires a long time in the process of calculating the income statement for the accounting department where the division is accounting must recap all invoice data. By designing the Point of sales (POS) Information system, it is hoped that it can simplify the sales process in which the creation and calculation of order forms automatically, report generation and also management of more organized sales data.